Analisis Pengaruh Letak Bahan terhadap Defleksi Balok Segi Empat dengan Tumpuan Engsel - Roll - Roll - Jasron, Jahirwan Ut (Jurnal Rekayasa Mesin, 2015)
Deflection is one of criteria in designing a construction. Analysis can be conducted by using several method and to obtain the more accurate result the process can be conducted by using a computer program. For comparison to evaluate the accurate of the analysis, a deflection test was conducted with a deflection test device.The exact analysis was conducted by using the three moment methods. The aim of this study is to analyze the effect of the lay out of load along the beam towards deflection. The deflection along the beam varied according on the load and its position. The deflection obtained for brass is 1,29 x 10-3 m, while for alluminium and steel are 1,25 x 10-3 m and 4,87 x 10-4 m, respectively.